Development of scoring application model and community-based total sanitation education (SESAMA) on stunting prevention behavior - Gustina, Mely; Saputra, Arie Ikhwan; Basthari, Rosalia Rina; Prijanto, Teguh Budi; Yorita, Epti; Suprijandani, Suprijandani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Nutritional Status Data Collection, the incidence of stunting in Indonesia is still high, same thing​ occurred in Bengkulu Province. The government has set total sanitation based community (STBM) as one of the intervention sensitive reduce stunting but Not yet successful. Knowledge, attitude low influential to behavior about hygiene sanitation including BABS. For That technology strategy is needed information For area remote through Application model development Scoring and Education Total sanitation based on SOCIETY (PEOPLE). Purpose: To develop Android -based SESAMA model design for behavior prevention of stunting in toddlers. Method: A quasi- experimental approach, specifically focusing on control group approach. The study took place from April to November 2024, in Enggano Island, North Bengkulu Regency. Using purposive sampling and the Isaac & Michael formula, 80 participants were selected and divided into two groups: 40 in the SESAME application model and 40 in the conventional health promotion, who met specific inclusion and exclusion criteria. The data was analyzed following a step-by-step process, beginning with a normality test using the kolmogorov smirnov test. With p-values greater than 0.05, the data was determined to follow a normal distribution. The analysis proceeded with a univariate test to determine the frequency distribution of participants characteristics, followed by bivariate analysis using wilcoxon, mann whitney, spearman rank and mancova. Results: The MANCOVA test results indicate a significant effect of the SESAMA application model intervention on mothers knowledge, attitudes, and behavior regarding stunting prevention. This is evidenced by a p-value of 0.000, which is smaller than the α value of 0.05 at a 95% confidence level. Conclusion: The Android-based SESAMA application has been validated as a valid, feasible, and effective tool for improving mothers' knowledge, attitudes, and behaviors regarding stunting prevention among children. The intervention significantly influenced these outcomes, addressing challenges in delivering education in isolated areas, particularly on hygiene and sanitation behaviors.